Asset Management Planning To Optimize Fixed Assets In The Printing Business Cv. Nusantara Kreasi - Fajarhya, Bagus; Ikraam, Ikraam; Dini, Maya (Universitas Dehasen Bengkulu, 2025)
Effective fixed asset management is an important element in supporting operational efficiency and sustainability, especially for small businesses such as printing. This study aims to analyze how asset management planning can optimize the utilization of fixed assets at CV. Nusantara Kreasi, a printing business in Palembang City. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation of the company's operational processes and asset conditions. The results of the study indicate that fixed asset management at CV. Nusantara Kreasi has been carried out simply and has not been systematically documented, machine maintenance is carried out periodically by the production team but not based on a structured schedule. However, there is awareness from the owner of the importance of maintaining asset conditions to support business productivity, this study also adapts the principles of ISO 55000 on a small business scale, such as value realization, assurance of capability, and lifecycle approach as a basis for compiling more focused and efficient planning steps.